An introduction to European intergovernmental organizations - Cogen, Marc (Routledge, 2016)
A reference to European intergovernmental organizations other than the European Union. It looks at the history of Non-EU organizations, their decision-making characteristics, membership policies, legal powers actions and interactions with each other and the European Union.